Power for dinner. Culinary diplomacy and geopolitical aspects in Portuguese diplomatic tables (1910-2023) - Cabral, Óscar; Lavrador, Luís; Orduna, Pablo; Moreira, Raquel (Frontiers in Political Science, 2025)
IntroductionThis paper examines how diplomatic meals in Portugal (1910–2023) have been shaped by Portuguese foreign policy and geopolitical contexts, and conversely, how Portuguese gastronomic culture has been leveraged as a culinary diplomacy and geopolitical rapprochement strategy. Framed within the theory of international relations, this paper examines how these meals promote transnational political relations, foreign affairs, and project Portuguese identity and soft power through national gastronomy.MethodsEmploying qualitative methods, the research analyses meal environments, highlighting the historical and cultural significance of the dining experience.ResultsThe findings reveal five distinct types of diplomatic meals, demonstrating that culinary practices have facilitated diplomatic negotiations while providing opportunities for cultural exchange and political messaging.DiscussionAlthough a clear culinary diplomacy strategy was not identified, this study enhances our understanding of the influence of transnational gastronomy on diplomacy, illustrating how national cuisines can be strategically employed to bolster a country’s global standing.